MiR-204 suppresses the progression of acute myeloid leukemia through HGF/c-Met pathway. Issue 1 (1st January 2021) - Nie, Dingrui; Ma, Ping; Chen, Yanli; Zhao, Huayan; Liu, Lin; Xin, Dao; Cao, Weijie; Wang, Fang; Meng, XiaoLi; Liu, Linxiang; Xie, Menghan; Sun, Ling
ABSTRACT: Acute myeloid leukemia (AML) was confirmed to be associated with hematopoietic insufficiency, as well as abnormal proliferation, diﬀerentiation or survival of myeloid progenitors. Multiple studies reported that microRNA-204 (miR-204) and Hepatocyte growth factor (HGF) played important roles in types of cancers. However, the potential molecular regulatory mechanism between miR-204 and HGF in AML remains to be further defined. Real-time PCR (RT-PCR) was adopted to detect the expression of miR-204 and HG. Relative protein levels were detected by western blot assay. The viability, cell cycle, apoptosis, migration, and invasion were analyzed by MTT, flow cytometry, and transwell assays. Moreover, the target relationship between miR-204 and HGF was predicted by MiRcode website and confirmed by luciferase reporter, RNA pull-down, and western blot assays. Our data suggested that miR-204 was downregulated in AML serum samples and cells. MiR-204 overexpression repressed cell proliferation, migration, invasion, and induced cell apoptosis in AML cells. HGF was upregulated in AML samples and cells, and HGF knockdown inhibited the malignancy of AML cells. In addition, HGF was directly targeted by miR-204. HGF overexpression reversed the effects of miR-204 mimic on AML cell proliferation, apoptosis, migration, and invasion. Besides, miR-204 regulated the c-Met signaling by targeting HGF, thereby regulating the downstream protein levels related to cell proliferation, apoptosis, migration, and invasion in AML cells. In conclusion, miR-204 could regulate AML progression through regulating the HGF/c-Met pathway.